Injuries Associated With Subsequent Child Maltreatment Diagnosis: By Age, Race, Gender, and Medicaid Status. (May 2022) - Negriff, Sonya; DiGangi, Mercie J.; Sharp, Adam L.; Wu, Jun
This study examined injuries that may precede a child maltreatment (CM) diagnosis, by age, race/ethnicity, gender, and Medicaid status using a retrospective case–control design among child members of a large integrated healthcare system ( N = 9152 participants, n = 4576 case). Injury categories based on diagnosis codes from medical visits were bruising, fractures, lacerations, head injury, burns, falls, and unspecified injury. Results showed that all injury categories were significant predictors of a subsequent CM diagnosis, but only for children < 3 years old. Specifically, fracture and head injury were the highest risk for a subsequent CM diagnosis. All injury types were significant predictors of maltreatment diagnosis for Hispanic children < 3 years, which was not the case for the other race/ethnicities. Overall, these findings suggest that all types of injury within these specific categories should have a more thorough assessment for possible abuse for children under 3 years. This work can inform the development of clinical decision support tools to aid healthcare providers in detecting abusive injuries.